Saussurian Binary Opposition as the Narrative Structure of Williams Summer and Smoke. - Anita Putri; Paulus Sarwoto (Universitas Sanata Dharma, 2016)
The Swiss linguist, Ferdinand de Saussure, is one of the forefathers of structuralism whose works have inspired and influenced many of current modern thinkers. Binary opposition is one of many of his thoughts. This notion came up from his theory explaining that in fact in humans attempt at deriving conceptual meanings, their minds work by distinguishing the differences between things. Thus, Saussure basically suggests the idea that humans first logical operation is by discerning things through their relationships; one of Saussures basic relationships is binary opposition. For this reason, this study is conducted to prove this basic yet comprehensive theory as the narrative structure of Williams Summer and Smoke. Tennessee Williams Summer and Smoke (1948) is chosen since it is richly endowed with binary symbols and characters. Moreover, the course of the narrative is also structured in dichotomies.The results of this study are: first, the binary symbols and characteristics found in the play reveal the dichotomies concerning the importance of soul/body, spirituality/sexuality, life/death, physical lust/divine love; second, the binary symbols and characters prove that the narrative structure of Summer and Smoke is constructed upon the binary oppositions as proven by the binary quests of soul and body and the binary role transformations between Alma and John as revealed by A.J. Greimas three pairs of actantial model.